Correction: Precision Public Health Campaign: Delivering Persuasive Messages to Relevant Segments Through Targeted Advertisements on Social Media - Jisun An (10230800) (2021)
Correction to: Precision Public Health Campaign: Delivering Persuasive Messages to Relevant Segments Through Targeted Advertisements on Social Media http://formative.jmir.org/2021/9/e22313/, published online 24 September 2021. In “Precision Public Health Campaign: Delivering Persuasive Messages to Relevant Segments Through Targeted Advertisements on Social Media” (JMIR Form Res 2021;5(9):e22313) the authors noted one error. The original article has been corrected. Other Information Published in: JMIR Formative Research License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2196/33922